A Student-as-Teacher Program: A Pathway to the Accountability of Medical Education Systems - Fatemeh Keshmiri (Kerman University of Medical Sciences, 2021)
Background: Teaching is identified as a necessary role and responsibility for junior faculty members in their future careers.Objectives: The present study aimed to test the hypothesis that a student-as-teacher (SaT) program can effectively prepare the students for their future roles as teachers and educators.Methods: In this quasi-experimental study, the participants included 143 postgraduate students of 12 doctorate and master's degree programs at Shahid Sadoughi University of Medical Sciences, who were selected by census method . Nine learning objectives were classified in four competencydomains: (1) adult learning principles; (2) instructional design; (3) teaching and learning processes; and (4) learner's assessment. The educational methods were based on an active learning approac.Results: The mean score of learners in the practical assessment was 12.5±3.6 out of 15, and their mean score in the modified essay test was 8.5±1.5 out of 10 after the educational intervention. The results showed that the scores of the learners' attitude about cooperative learning were significantly different before (2.38±0.31) and after (4.15±0.65) the intervention (P=0.0001). Also, the scores of learners' capabilities in teaching were significantly different before (2.5±0.61) and after (3.80±0.34) the intervention (P=0.0001). The learners considered their teaching capabilities to be at the level of "familiarity without mastery" and "implementation mastery" before and after the intervention, respectively (P=0.0001).Conclusion: It is recommended to develop and implement SaT programs to improve the teaching capabilities of students using innovative teaching methods and prepare them for their future roles as instructors and teachers.